S128 The Extrinsic Coagulation Pathway is Locally Upregulated in an Experimental Model of Viral Exacerbation of Pulmonary Fibrosis. (19th November 2012) - Smoktunowicz, N; Alexander, R; Franklin, L; Williams, AE; Jarai, G; Scotton, CJ; Mercer, PF; Chambers, RC
Abstract : Introduction: Acute exacerbation (AE) of idiopathic pulmonary fibrosis (IPF) is defined as an episode of acute respiratory worsening without an identifiable aetiology. Herpes viruses infections have been implicated as a possible cause of AE in IPF. Moreover, herpes viruses have been shown to act as developmental cofactors and exacerbating agents in experimental pulmonary fibrosis. There is growing evidence that the local activation of the coagulation cascade mediates potent profibrotic effects via the activation of proteinase activated receptors (PARs) and thereby contributes to the development of pulmonary fibrosis (Scotton et al, J Clin Invest. 2009, 119). We hypothesised that viral infections promote the local activation of the coagulation cascade and influence the progression of established experimental pulmonary fibrosis. Methods: C57BL/6 mice were infected with γ-herpesvirus (γHV68) or given saline 14 days after oropharyngeal bleomycin (1mg/kg) instillation. The mRNA and protein levels of coagulation factors in lung tissue homogenates were assessed by qPCR and immunohistochemistry, respectively. Total lung collagen was quantified by assessing lung hydroxyproline levels by HPLC at 7 and 14 days post inoculation (p.i). Results: Tissue factor (TF) and factor X (FX) mRNA levels were increased in the lungs of bleomycin-γHV68 infected mice at day 7 p.i. compared with bleomycin alone treated animals. This upregulation was associated with increased TF and FX protein immunoreactivity, which was localised to bronchial and hyperplastic alveolar epithelium and appeared to persist at 14 days p.i. Total lung collagen levels were also increased in bleomycin-γHV68 infected animals at 14 days p.i. (p<0.01) compared to bleomycin alone treated mice. Conclusions: γHV68 infection in established pulmonary fibrosis exacerbates the fibrotic response as evidenced by the increased deposition of total lung collagen. This is preceded by an amplification of the local activation of the extrinsic coagulation cascade. A recent clinical trial suggests that systemic anticoagulant therapy (warfarin) increases mortality in IPF (Noth et al, Am J Respir Crit Care Med. 2012, 186). The coagulation cascade may therefore play both protective and deleterious roles in pulmonary fibrosis. We propose that future anticoagulant interventions may need to be directed at selectively targeting local profibrotic signalling responses.